Optimization Design of Steering Mechanism for Carbon-free Car based on Matlab - Linsong Li; Wenguang Wu (Jixie chuandong)
In order to improve the track symmetry of carbon-free car for ‘S’ shape， the movement mechanism of the car is designed， the mathematical optimization model of the steering mechanism is built， and the relevant parameter is optimized by using the Matlab Optimization Tools， the influence between parameter and track symmetry is discussed. The accuracy of the optimized parameter is confirmed by ADAMS simulation， the track symmetry achieved 96% theoretically. The test shows that the car can avoid 20 obstacles which verified the rationality of the mechanism.